2010
DOI: 10.1108/00070701011058226
|View full text |Cite
|
Sign up to set email alerts
|

Towards a cross‐cultural typology of trust in B2B food trade

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Hofstede, Fritz, Canavari, Oosterkamp, and Sprundel (2010) conducted a study to develop a detailed trust typology and argued that trust is a culture-specific phenomenon because the societies are different from one another. Erdem and Aytemur (2014) conducted a study on the Turkish business organizations and demonstrated that the cultural tendencies in a trust relationship might change the expectations of parties.…”
Section: Discussionmentioning
confidence: 99%
“…Hofstede, Fritz, Canavari, Oosterkamp, and Sprundel (2010) conducted a study to develop a detailed trust typology and argued that trust is a culture-specific phenomenon because the societies are different from one another. Erdem and Aytemur (2014) conducted a study on the Turkish business organizations and demonstrated that the cultural tendencies in a trust relationship might change the expectations of parties.…”
Section: Discussionmentioning
confidence: 99%
“…Formalization of these relationships, however, is at a developmental stage and the general situation in fresh produce partnership is informality, or at best loose agreement, as opposed to binding contractual and financial agreement [4,9]. The informality of the relationships between fresh produce supply chain actors triggers the use of other contract-based coordination mechanisms in order to ensure the smooth functioning of the relationship [9,11,12]. As a result, trust and commitment seem to be key regulators of relationships within the fresh produce supply chain; however, the complexity of food supply chain business partnerships makes it critical to pay attention to the many facets that are involved in the trust that each part places in the other, which usually involve the implementation of quality control systems along the chain [11].…”
Section: Literature Review Of Fresh Food Supply Chain Management: Colmentioning
confidence: 99%
“…The informality of the relationships between fresh produce supply chain actors triggers the use of other contract-based coordination mechanisms in order to ensure the smooth functioning of the relationship [9,11,12]. As a result, trust and commitment seem to be key regulators of relationships within the fresh produce supply chain; however, the complexity of food supply chain business partnerships makes it critical to pay attention to the many facets that are involved in the trust that each part places in the other, which usually involve the implementation of quality control systems along the chain [11]. In this way, trust mechanisms are reinforced with quality control over the business models and products supplied by any upstream supplier, downstream customers, or logistic service firm.…”
Section: Literature Review Of Fresh Food Supply Chain Management: Colmentioning
confidence: 99%
See 2 more Smart Citations